Metatese cruzada de arilpropenos de ocorrência natural com acrilatos para a síntese de produtos da química fina - Alexandra Goncalves Santos (2013)
In this work, the reactions of cross-metathesis of substrates of natural origin (anethole, isoeugenol and isosafrole) were studied with the following acrylates: methyl acrylate, ethyl acrylate and 2-ethylhexyl acrylate in a solvent-free system, with excess acrylate and employing the catalysts: Grubb-Nolan [dichloro (2,5-dimesitylimidazolyl-ilidene) (tricyclohexylphosphine) benzylideneruthenium (II)] and Hoveyda-Grubbs second generation [dichloro (3,4-dihidro-dimesitylimidazolyl-ilidene) 2- isopropoxihenylilideneruthenium (II)] These reactions were aimed for the synthesis of products which have significant commercial applications, the cinnamates, UV absorbing molecules and ferulates, molecules with antioxidant properties, anti-inflammatory and anticancer. The reactions performed using the Grubbs-Nolan catalyst in a system without solvent and with an excess of acrylate occur only with the addition of phenols. Phenols improve the activity the system and minimize the formation of homodimers. The phenols tested were: 2-tert-butylphenol, 4-tert-butylphenol and 2,6 tert-butylphenol. The 4-tert-butylphenol showed the best performance. Under the best conditions, yields for cinnamates and ferulates from 89% to 99% were obtained by using 2.8 mol% [dichloro (2,5-dimesitylimidazolyl-ilidene) (tricyclohexylphosphine) benzylideneruthenium (II)], 4 hours of reaction at 70 °C and with the addition of 500 equivalents of 4-tert-butylphenol in the reactions in the presence of anethole and isosafrole and of 18 equivalents of this phenol in the presence isoeugenol. The reactions using the second generation Hoveyda-Grubbs catalyst were carried out without addition of phenol. Under the best conditions, the ferulates and cinnamates were obtained in yields of 91% and 100% using 0.5 mol% [dichloro (3,4-dihidro-dimesitylimidazolyl-ilidene) 2- isopropoxihenylilideneruthenium (II)] in solvent-free system, with an excess of acrylate and 4 hours of reaction at 70 °C. By using 0.1 mol% of this catalyst under the same reaction conditions above yields of 73% to 88% for cinnamates and ferulates were obtained. The cross-metathesis of the propenyl benzenes (anethole, isosafrole and isoeugenol) with methyl, ethyl and 2-ethylhexyl acrylates is a short, highly efficient and sustainable route for the synthesis.